Good nature : why seeing, smelling, hearing, and touching plants is good for our health - Willis, K. J. (Pegasus Books, 2024)
"Good Nature reveals how, if we bring nature more into our lives, it can help improve our health and well-being in so many unexpected ways. Oxford professor Kathy Willis has spent her career researching fossilised plants and plant matter - but when she stumbled across a study that showed that patients recovering from surgery improved faster just by being able to see trees from their hospital bed, it radically changed the way she viewed the natural world. Professor Willis has since embarked on a process of discovery to find the research that has shown, time and time again, that there is a causal link between plants in our lives, both indoors and outside, and better physical and mental health. Consulting plant scientists and biologists, medical practitioners and psychiatrists, city planners and government health authorities, she encourages us to transform how we design and inhabit our environments. There are simple changes we can all make in our homes: for example, the scent of rosemary will make you more awake; green-and-yellow-leaved houseplants are the best at reducing stress; and touching and stroking untreated wooden surfaces can lower our blood pressure. But we can also think on a much grander scale: prescribing more nature in streets, offices and our homes will not only save money but improve the health of us all. Focusing on how we interact with nature through the senses of sight, smell, hearing and touch, Good Nature explains how we can organize our homes, our time outdoors and the world around us to reap the health benefits of nature that science is only now just discovering"--